1992
DOI: 10.1002/pros.2990200206
|View full text |Cite
|
Sign up to set email alerts
|

Prostate specific antigen and prostatitis II. PSA production and release kinetics in vitro

Abstract: Elevations in serum prostate specific antigen (PSA) levels in patients with prostatitis are well known, but the pathophysiologic mechanisms involved with this phenomenon are poorly understood. We have recently evaluated the effect of prostatitis on PSA levels in primates. This data demonstrated a rapid rise in PSA, which subsequently fell along the biological decay curve. This suggested a release of sequestered PSA. We evaluated the effect of infection upon PSA production for the prostatic adenocarcinoma cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…It has been shown that the human prostate cancer cell line LNCaP, when infected with live E. coli bacteria or when treated with heat-killed bacteria or lipo-polysaccharide and bacterial culture supernatants in vitro, did not lead to an increased expression of PSA [20]. This suggested that these bacterial factors did not lead to an increased synthesis of PSA.…”
Section: Acute Bacterial Prostatitis and Serum Prostate-specific Antigenmentioning
confidence: 93%
“…It has been shown that the human prostate cancer cell line LNCaP, when infected with live E. coli bacteria or when treated with heat-killed bacteria or lipo-polysaccharide and bacterial culture supernatants in vitro, did not lead to an increased expression of PSA [20]. This suggested that these bacterial factors did not lead to an increased synthesis of PSA.…”
Section: Acute Bacterial Prostatitis and Serum Prostate-specific Antigenmentioning
confidence: 93%
“…Brawn et al [10]reported that in 105 autopsy cases, 50% of the cases with a serum PSA higher than 4.0 ng/ml had acute or chronic prostatitis compared to 22% without inflammation. Moon et al [11]did not observe an increase in PSA production in LNCaP cell line when infected with bacteria in vitro, and they suggested that infection and inflammation would increase serum PSA concentrations by affecting the natural anatomical and physiological barriers to PSA diffusion between the prostatic glandular tissue and the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the human prostate cancer cell line LNCaP, when infected with live E. coli bacteria or when treated with heat-killed bacteria or lipo-polysaccharide and bacterial culture supernatants in vitro, did not lead to an increased expression of PSA [20]. It has been shown that the human prostate cancer cell line LNCaP, when infected with live E. coli bacteria or when treated with heat-killed bacteria or lipo-polysaccharide and bacterial culture supernatants in vitro, did not lead to an increased expression of PSA [20].…”
Section: Acute Bacterial Prostatitis and Serum Prostate-specific Antigenmentioning
confidence: 99%